2015
DOI: 10.1128/jcm.02015-15
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Diversification and Changes in Lipid Traits and Colony Morphology in Mycobacterium abscessus Clinical Isolates

Abstract: fThe smooth-to-rough colony morphology shift in Mycobacterium abscessus has been implicated in loss of glycopeptidolipid (GPL), increased pathogenicity, and clinical decline in cystic fibrosis (CF) patients. However, the evolutionary phenotypic and genetic changes remain obscure. Serial isolates from nine non-CF patients with persistent M. abscessus infection were characterized by colony morphology, lipid profile via thin-layer chromatography and matrix-assisted laser desorption ionization-time of flight mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Importantly, mutations abrogating MmpL4a activity, such as the one described here, are of clinical relevance. Indeed, a recent study reporting the evolutionary phenotypic and genetic changes in serial isolates from patients infected with M. abscessus identified detrimental single point mutations in mmpL4a , leading either to a premature stop codon or to a frameshift mutation (Park et al ., ). Interestingly, these mutations in MmpL4a, also leading to the loss of GPL, occurred essentially during the chronic lung infection with M. abscessus (Park et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, mutations abrogating MmpL4a activity, such as the one described here, are of clinical relevance. Indeed, a recent study reporting the evolutionary phenotypic and genetic changes in serial isolates from patients infected with M. abscessus identified detrimental single point mutations in mmpL4a , leading either to a premature stop codon or to a frameshift mutation (Park et al ., ). Interestingly, these mutations in MmpL4a, also leading to the loss of GPL, occurred essentially during the chronic lung infection with M. abscessus (Park et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…While several studies have been published on TAG accumulation in M. tuberculosis, very little is known about this process in NTM for which only a few studies have focused on the model rapid-growing species M. smegmatis (Garton et al, 2002;Dhouib et al, 2011). However, a recent study reported the increased TAG production and accumulation in clinical M. abscessus strains isolated from CF patients suffering from a longer period of lung infection as compared to those suffering from a shorter period (Park et al, 2015). This observation allowed the authors to propose that TAG accumulation may be a phenotype associated with the long-term survival of M. abscessus in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing uncovered a mutation in the mmpL4a gene, which led to the substitution Tyr842His. In M. abscessus , a similar mutation was described recently (Park et al ., ). In M. abscessus , and also in M. bolletii , mmpL4 is part of the gene cluster responsible for the biosynthesis and transport of surface‐associated glycopeptidolipids (GPL) (Ripoll et al ., ).…”
mentioning
confidence: 97%